Closet Virtues: Ethics of Concealment in English Anglicanism. Issue 3 (27th May 2022) - Coleman, Simon
ABSTRACT: I trace interrelations and tensions between varied practices of concealment and discernment in the Church of England by examining contrasting attitudes to sexuality among Anglo-Catholics and Evangelicals. Moral panics over the sexual orientations of priests point to wider conflicts over incarnation, mediation, communication and knowledge. Combining historical and ethnographic data on the Church in England and the global Communion, I explore what can and should be openly 'known' in Anglican circles. I link my analysis of the Anglican case to wider considerations of what anthropology can and cannot claim to 'know' and discern through ethnographic observation, description and analysis.